2012
DOI: 10.4274/jcrpe.768
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Frequency of HLA DR-DQ Haplotypes Among Children and Adolescents with Type 1 Diabetes Mellitus in the Southeast Region of Turkey

Abstract: Objective: The aim of this study was to determine the frequency of HLA DR-DQ haplotypes in children with type 1 diabetes mellitus (T1DM) in the Southeast Region of Turkey.Methods: Eighty children and adolescents with T1DM and eighty control subjects participated in the study. HLA-DR, DQ was typed using polymerase chain reaction and sequence-specific priming technique.Results: HLA DRB1*03 allele was significantly more common in patients than in control subjects. HLA DRB1*11, HLA DRB1*13 and HLA DRB1*14 allele f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
8
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
3
8
0
1
Order By: Relevance
“…There was no significant correlation between diabetes‐associated autoantibodies and ethnicity, confirming some previous studies in MC , Latinos, African Americans, Caucasians, and Saudi Arabians . However, it has been shown that patients with T1D born to immigrants to Sweden have different HLA‐DQ haplotypes and genotypes, as well as beta‐cell autoantibodies (predominance of GADA), compared to native Swedish patients .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…There was no significant correlation between diabetes‐associated autoantibodies and ethnicity, confirming some previous studies in MC , Latinos, African Americans, Caucasians, and Saudi Arabians . However, it has been shown that patients with T1D born to immigrants to Sweden have different HLA‐DQ haplotypes and genotypes, as well as beta‐cell autoantibodies (predominance of GADA), compared to native Swedish patients .…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence of HLA‐DQ haplotypes and genotypes associated to T1D may vary according to ethnicity. Analysis of distinct ethnic groups has shown different associations between Caucasian, Hispanic, and Black populations . Moreover, the prevalence of high‐risk genotypes can change over time, in the same region .…”
mentioning
confidence: 99%
“…Following early reports in 1980s on annotation of high‐ and low‐risk HLA class II (DR‐DQ) haplotypes for type 1 diabetes, a huge number of studies affirmed that the highest risk for developing the disease is conferred by heterozygous DR3 (DRB1*03:01 – DQB1*02:01)/DR4 (DRB1*04:01/02/04/05/08 – DQB1*03:02) genotypes relative to homozygotes DR3/DR3 and DR4/DR4 genotypes (Noble & Valdes, ; Park & Eisenbarth, ; Eisenbarth, ; Svejgaard & Ryder, ; Keskin et al ., ). More precisely, among over 50 different loci that influence susceptibility to type 1 diabetes, the HLA region particularly class II alleles was found to be the strongest predictor of disease risk (Park et al ., ; Park & Eisenbarth, ; Noble & Valdes, ; Onengut‐Gumuscu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, analysis of HLA class II alleles and haplotypes frequency in a sample of Iranian population not only confirms previous reports from the country (Sayad et al ., ; Rabbani et al ., ) but also is in line with several results observed in other Caucasians including Turkish (Saruhan‐Direskeneli et al ., ; Keskin et al ., ), Italian (Petrone et al ., ), German (Donner et al ., ) and Macedonian (Ilonen et al ., ) and even some of non‐Caucasian populations such as Asians (Park & Eisenbarth, ; Bugawan et al ., ) and Tunisians (Fekih Mrissa et al ., ). As expected, we found that DRB1*03:01, DRB1*04:02 and DQB1*02:01, DQB1*03:02 are highly significant disease‐associated alleles among our patients with T1D.…”
Section: Discussionmentioning
confidence: 99%
“…A small study with low-resolution genotyping on patients and controls from southeast Turkey reported a strong predisposing effect for DQB1*02 and for the presumed haplotype DRB1*03-DQB1*02 [35]. DQB1*03 was reported as significantly protective; however, the low-resolution genotyping of the study precluded distinction of the DQB1*03:01 (commonly type 1 diabetes protective) from the DQB1*03:02 (commonly type 1 diabetes predisposing) allele.…”
Section: Discussionmentioning
confidence: 99%